Community interpreting in Poland. Formal legislation, role and opportunities. - Krysztofowicz, Dominika; Krupienicz, Zofia (International Journal of Language, Translation and Intercultural Communication, 2016)
Community interpreting is a new and still developing field of research in Poland. With the outbreak of the Ukrainian Crisis in 2014, followed by the Refugee Crisis in 2015, its role has become especially crucial and apparent. However, more detailed formal legislation in that regard is still lacking. There are also many complex issues connected with the perception of community interpreting in Poland. The paper will focus on the actual status of community interpreting in Poland, in connection to already existing formal legislation, role and possible work opportunities in the field of community interpreting.